Roots of nationhood : the archaeology and history of Scotland - Campbell, Louisa,; Wright, Dene,; Hall, Nicola A., (Archaeopress Publishing Ltd, 2018)
12 papers from specialists covering a wide array of time periods and subject areas, this volume explores the links between identity and nationhood throughout the history of Scotland from the prehistory of northern Britain to the more recent heralding of Scottish identity as a multi-ethnic construction and the possibility of Scottish independence.